Protocolos para la reproducción inducida de Myleus schomburgkii (Jardine, 1841), usando extracto pituitario de carpa, conceptal y ovaprim - Bernuy Rodríguez, Alfonso (2023)
The objective of the present study was to determine the effect of three hormonal inducers (EPC, Conceptal®, and Ovaprim®) on spawning induction and spermiation in the reproduction of black-winged palmetto Myleus schomburgkii, (0.70 ± 0.10 kg of weight and 27.81 ± 1.25 cm in length in males and 0.72 ± 0.29 kg in weight and 28.84 ± 3.56 cm in length in females). The reproducers were captured from the natural environment (Downstream community Santa Clara River Nanay) and transported to the facilities of the "Fernando Alcántara Bocanegra" Research Center of the IIAP, Iquitos. The protocols were applied in a 12-hour interval, which were performed in two doses (the first 10% of the total calculated and the second 90% of the total dose calculated): T1 (EPC): 6 mg / kg in females and 2 mg / kg in males; T2 (Conceptal) 2.5 ml / kg in females and 1.5 ml / kg in males and; T3: (Ovaprim) 0.50 ml / kg in females and 0.25 ml / kg in males. A positive effect on ovulation was found in 66.6% in T1 and 11.1% in T2, results corroborated with the analysis of variance, determining significant differences (P 0.05). Likewise, significant differences were also reported in the analysis of oocyte diameter in different months of evaluation. Spawning occurred at 27 hrs (using EPC) after the final induction dose of 4.52 g and 208.80 (mean egg count / 1 g of spawning) and fecundity of 942.03 were applied. Fertilized eggs had positive results.using fish tanks with zero flow at 40 hours.